A study of Geomagnetic Field and It's secular variation at the Location Brazilian Anomaly (25Â°S, 45Â°W). - AI-Mahdi, H.A.; Mokheber, A.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
ln this paper we study  and  analysis  the  total intensity  (P) .and the horizontal  component (H) of the geomagnetic field at the location na ly Brazilian    Anomaly  (Lat   25S,    long   4SÂ·"W)    in  which   the geomagnetic field intensity  has a minimum  value. We examine the relationship. between  the { F , H) with altitude  at a certain latitude, and.relationship  between  ( F,H ) with  the latitude  at  the certain  altitude.We study  also  the nature  of the secular  variation  of the geomagnetic field  at the same  locat.ion  dpning one century  (1900-2000) , we found that  the rate  of change  of  field  inten5ity  (F). is roughly  (9.3   % per century).The  geomagnetic field  data  is obtained   by  using  JGRF1 0  model  atBrazilian anomaly (long 45"W).